2016
DOI: 10.18805/ajdfr.v35i2.10721
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pectin coating on colour and quality of dehydrated pineapple during storage

Abstract: The effect of storage on the colour and quality parameters of uncoated and pectin coated dehydrated pineapple samples were studied during storage. The dehydrated pineapple samples were packed in aluminium foil pouches and stored at 30 ± 1°C and 75% RH. The colour change was determined using L*, a*, b*, hue, total colour difference and browning index values. The kinetics of changes in colour parameters was determined using zero-order and first-order reaction kinetics. Non-linear regression of experimental data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…This demonstrates that the color of the dried coconut chips degraded linearly. Similarly, several authors have reported in the literature that zero-order kinetic models can predict color parameter changes in a linear format during storage (e.g., for pineapple [15], button mushrooms [29] and kiwi [7]). For dried coconut chips, the kinetic rate constants of the color parameters were slower at 35 • C than at 45 or 55 • C by 0.67 and 0.60 times for the L* value, 0.18 and 0.08 times for the a* value, 0.53 and 0.28 times for the b* value, 0.57 and 0.35 times for the ∆E value and 0.43 and 0.19 times for the BI, respectively.…”
Section: Kinetics Of the Quality Parameter Of Dried Coconut Chips Dur...mentioning
confidence: 80%
See 2 more Smart Citations
“…This demonstrates that the color of the dried coconut chips degraded linearly. Similarly, several authors have reported in the literature that zero-order kinetic models can predict color parameter changes in a linear format during storage (e.g., for pineapple [15], button mushrooms [29] and kiwi [7]). For dried coconut chips, the kinetic rate constants of the color parameters were slower at 35 • C than at 45 or 55 • C by 0.67 and 0.60 times for the L* value, 0.18 and 0.08 times for the a* value, 0.53 and 0.28 times for the b* value, 0.57 and 0.35 times for the ∆E value and 0.43 and 0.19 times for the BI, respectively.…”
Section: Kinetics Of the Quality Parameter Of Dried Coconut Chips Dur...mentioning
confidence: 80%
“…The values are reported as L* (degree of brightness to darkness), a* (degree of redness (+) to greenness (−) and b* (degree of yellowness (+) to blueness (−). The total color difference (∆E) and browning index (BI) were calculated according to Saini and Sharma [15] using the following formulas:…”
Section: Quality Analysis 231 Color Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, many variables promote the deterioration and waste of fruits during storage, including environmental factors [8], harvest time, the stage of fruit maturity, and the occurrence of mechanical damage throughout handling phases [9]. Previously, coating techniques have been implemented to improve the shelf life and quality of fruits and vegetables [10], or to develop deliberate cucumber characteristics throughout the selling chain for consumers [11]. However, deciding on the right coating blend assuredly affects the performance of other coating layers.…”
Section: Introductionmentioning
confidence: 99%
“…It can be administered in a variety of ways, including dipping, misting, or packing [12]. When treating bunches, it is also used to increase their quality [13]. However, the appropriate coating has a favorable influence on many quality traits.…”
Section: Introductionmentioning
confidence: 99%